LEGAL CONSEQUENCES OF BANKRUPTCY AND POSTPONEMENT OF DEBT PAYMENT OBLIGATIONS: ARE THEY SIMILAR? - Bicar Franki Leonardo Manurung; Elza Syarief; Rina Shahriyani Shahrullah (Universitas Internasional Batam, 2022)
There is a main difference between the Postponement of Debt Payment Obligations/ PDPO (Penundaan Kewajiban Pembayaran Utang/PKPU) and bankruptcy. They may become a solution when a business is entangled in financial problems or debts. Due to their differences, this study aims to ascertain the legal consequences arising from bankruptcy and the Composition Plan under the PDPO by analysing the court decision relating the Homologation Decision (the Endorsed Composition Plan). It adopts normative juridical research, therefore the data used is secondary data. Data collection techniques are a literature study in the form of legislation and literature and document study, especially the decision No.9/Pdt.Sus-Pailit/2020/PN Smg in conjunction with No.13/Pdt.Sus-PKPU/2016/PN Smg. It uses a qualitative descriptive analysis method. The study found that both the bankruptcy and PDPO have legal consequences on debtors and relevant stakeholders. The PDPO based on the Composition Plan results in the bankruptcy of a company if it still does not pay the debt as stipulated in the Homologation Decision (the Endorsed Composition Plan).